SPRITUALITAS GURU SEKOLAH DASAR: PERCIKAN MANGUNWIJAYA - Vinsensius Sumardi (PGSD UNIKA SANTU PAULUS RUTENG, 2017)
Ideally, teacher is an important figure for the success of all educational processes in any education level. In the primary school, the presence of teacher cannot be neglected. In this level, a good teacher takes such roles as father, mother, brother and friend for young learners. On the other hand, the primary school teachers do not act as lecturer, trainer, and science guard. In this case, the acts of giving commands, imposition, pressure, and indoctrination should be avoidable. This writing overviews constructive ideas on education of Mangunwijaya eventhough it is very simple and far from ideal concepts. Hopefully, this writing is useful for those who care education.